A Review of the Techniques Used to Reduce the Thermal Load of Buildings in Mexico's Warm Climate - Ramírez Dolores, César; Andaverde Arredondo, Jorge Alberto; Alcala, Gerardo; Velasco Tapia, Fernando; López Lievano, Daniel (Italian Association of Chemical Engineering, 2020)
The heat transfer of buildings contributes directly to the consumption of electricity, because the most common alternative to reduce the internal temperature has been the disproportionate use of conventional air conditioning systems. The bioclimatic architecture is an alternative of a still limited application. However, nowadays, several investigations indicate a significant correlation between heat gain and internal thermal comfort perceived in built spaces. This proposal reviews the techniques studied and used to reduce the thermal load coming from outside and generated inside buildings located in a warm weather zone in Mexico. These cases are intended to show the current status of this research topic, as well as identify areas of opportunity relevant to the analysis and its implementation especially in coastal areas. Critical factors to explore include the influence of relative humidity on the thermal sensation, as well as warm geographical and climatic conditions, which can be humid tropical or arid and dry.